1969
DOI: 10.2136/sssaj1969.03615995003300040029x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Potassium in the B Horizon Clay of Some Prairie Loess Soils of the Midwest

Abstract: To test the hypothesis that K content of Iowa soils was related to soil development, samples from the B horizon of selected sites were obtained from loess‐derived prairie soils at several locations within the state. Samples were also obtained from Nebraska and Illinois loess soils to relate the Iowa study to the midwestern prairie region. Total K in clay from the B horizons decreased progressively from west to east. This was explained on the basis of concurrent increase in average annual precipitation from wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Regional variation in soil total K content occurs in Iowa. Soils in southern and western Iowa have higher total K content than soils in eastern Iowa (Wells and Riecken, 1969). Much of the available Iowa soil profile K data are from the pioneering work of Hanway and others (Hanway, 1961, 1962; Hanway and Scott, 1957).…”
Section: Methodsmentioning
confidence: 99%
“…Regional variation in soil total K content occurs in Iowa. Soils in southern and western Iowa have higher total K content than soils in eastern Iowa (Wells and Riecken, 1969). Much of the available Iowa soil profile K data are from the pioneering work of Hanway and others (Hanway, 1961, 1962; Hanway and Scott, 1957).…”
Section: Methodsmentioning
confidence: 99%
“…In an average year profi P es in the low rainfall sequence late chemical weathering and leaching intensifies this i y removing the POTASSIUM STATUS O F SIX LOESSIAL SOILS than weathering intensity in the release of K and, hence, ultimately soil K status. Jackson (1964)~ Wells and Riecken (1969), and Somasiri et al (1971) have indicated that pedogenic processes are sensitively reflected in the quantity and nature of the clay fraction. But in this weakly weathering zone the quantity of clay is determined chiefly by depositional traits, and only the type of clay reflects the pedogenic influences.…”
Section: Discussionmentioning
confidence: 99%
“…Feldsparas microcline ("K-feldspar") or plagioclase ("Ca-feldspar") comprise 10 to 20% of the sand and silt fractions, with plagioclase contents being fairly variable. For the Fayette and Ida profiles the amounts and distribution of quartz and feldspars are explained by Wells and Riecken (1969) as reflecting more intense pedological weathering of loess in eastern Iowa (where Fayette is located) than in western Iowa (where Ida is located). The more intense weathering in eastern Iowa is the result of higher rainfall causing more intense leaching and supporting forest vegetation (Wells and Riecken, 1969;Ruhe, 1984;Muhs et al, 2001).…”
Section: Resultsmentioning
confidence: 98%
“….2 Semiquantitative percentages of size fractionated silicate mineralogy with depth for the Harps, Ida and Fayette series based upon interpolation, extrapolation and interpretation of mineralogy given for Iowa soils in Khan (1991), Wells (1963), Wells and Riecken (1969), Ruhe (1984) and USDA-NRCS KSSL database (2015). ............................................................... Table 3.3 Silicate minerals identified in Iowa soils by Khan (1991), Wells and Riecken (1969) and Ruhe (1984) Table 3.4 Semiquantitative Si content partitioned by size fraction and with depth for Harps, Fayette and Ida soil series of Iowa. Contents calculated using data and information provided in Tables 3.1 through 3.3.…”
Section: List Of Tablesmentioning
confidence: 99%